Antiproliferative Activity of Double Point Modified Analogs of 1,25-Dihydroxyvitamin D(2) Against Human Malignant Melanoma Cell Lines - Piotrowska, Anna (Int J Mol Sci, 2016)
Vitamin D is a lipid soluble steroid hormone with pleiotropic biological properties, including regulation of cell proliferation, differentiation and apoptosis. As to these desirable anticancer actions, 1,25-dihydroxyvitamins D and analogs have been reported to inhibit the proliferation and to induce differentiation of a wide variety of cancer cell types, including human malignant melanoma. However, there is a need for novel and more efficacious vitamin D analogs, and how best to design such is still an open issue. A series of double point modified (DPM) analogs of 1,25-dihydroxyvitamin D(2) (1,25(OH)(2)D(2)) induced differentiation of the vitamin D receptor (VDR) positive A375 and VDR negative SK-MEL 188b human malignant melanoma cell lines. Surprisingly, the dose of 1,25(OH)(2)D(2) required to inhibit the proliferation of the A375 melanoma cell line by was several fold lower than that required in the case of 1,25(OH)(2)D(3). To evaluate the impact of the modification in the side chain (additional 22-hydroxyl) and in the A-ring (5,6-trans modification), the regular side-chain of vitamin D(2) or D(3) was retained in the structure of our analogs. As expected, 5,6-trans modification was advantageous to enhancing the anti-proliferative activity of analogs, but not as a single point modification (SPM). Very unexpectedly, the additional 22-hydroxyl in the side-chain reduced significantly the anti-proliferative activity of both the natural and 5,6-trans series analogs. Finally, an induction of pigmentation in melanoma SK-MEL 188b cells was observed to sensitized cells to the effect of vitamin D analogs.